Gender Equity and Due Process in Campus Sexual Assault Adjudication Procedures. (23rd February 2023) - Porter, Kamaria B.; Levitsky, Sandra R.; Armstrong, Elizabeth A.
ABSTRACT: Title IX prohibits sex discrimination in federally funded education programs. In 2011, the Department of Education under President Obama issued a Dear Colleague Letter (DCL) advising schools of their obligation to protect Title IX rights by more effectively responding to campus sexual assault. Many observers hoped that this would promote gender equity. Yet it also generated a backlash, as critics charged schools with stripping accused students of due process rights in campus adjudication procedures. We conducted content analysis of the 2016–17 sexual misconduct policies of 381 American colleges and universities to analyze how well adjudication procedures created in response to the DCL attended to both gender equity and due process requirements. The state of adjudication at this pivotal moment provides an empirical baseline from which to assess equity in university sexual misconduct procedures. We found that most school procedures for investigating and adjudicating complaints of sexual misconduct included hybrid models that incorporated due process protections while acknowledging (but often not fully meeting) Title IX obligations. To our knowledge, this is the only large-scale national study of how schools have reconciled Title IX and due process rights in adjudication procedures.